Stage II Chronic Maxillary Atelectasis Associated with Subclinical Visual Field Defect - Mangussi-Gomes, João; Nakanishi, Márcio; Chalita, Maria Regina; Damasco, Fabiana; De Oliveira, Carlos Augusto Costa Pires (International Archives of Otorhinolaryngology, 2013)
Introduction Chronic maxillary atelectasis (CMA) is characterized by a persistent decrease in the maxillary sinus volume due to inward bowing of its walls. According to its severity, it may be classified into three clinical-radiological stages.Objective To report a case of stage II CMA associated with subclinical visual field defect.Case Report A 34-year-old woman presented with a 15-year history of recurrent episodes of sinusitis and intermittent right facial discomfort for the past 5 years. She denied visual complaints, and no facial deformities were observed on physical examination. Paranasal sinus computed tomography (CT) demonstrated a completely opacified right maxillary sinus with inward bowing of its walls, suggesting the diagnosis of stage II CMA. A computerized campimetry (CC) disclosed a scotoma adjacent to the blind spot of the right eye, indicating a possible damage to the optic nerve. The patient was submitted to functional endoscopic sinus surgery, with drainage of a thick mucous fluid from the sinus. She did well after surgery and has been asymptomatic since then. Postoperative CT was satisfactory and CC was normal.Discussion CMA occurs because of a persistent ostiomeatal obstruction, which creates negative pressure inside the sinus. It is associated with nasosinusal symptoms but had never been described in association with any visual field defect. It can be divided into stage I (membranous deformity), stage II (bony deformity), and stage III (clinical deformity). The silent sinus syndrome is a special form of CMA. This term should only be used to describe those cases with spontaneous enophthalmos, hypoglobus, and/or midfacial deformity in the absence of nasosinusal symptoms.
Keywords: paranasal sinus diseases; maxillary sinus; visual fields; maxillary diseases